TP53 and PIK3CA gene mutations in adenocarcinoma, squamous cell carcinoma and high-grade intraepithelial neoplasia of the cervix - Tornesello, Maria Lina (BioMed Central, 2014)
BACKGROUND: Mutations in the tumor suppressor gene TP53 and proto-oncogene PIK3CA and alterations of p53 and PIK3CA AKT mTOR pathways are common events in several human cancers. We focused on the analysis of TP53 and PIK3CA gene variations in adenocarcinoma, squamous cell carcinoma as well as in intraepithelial neoplasia grade 3 of the cervix. METHODS: DNA samples from 28 cervical adenocarcinoma, 55 squamous cell carcinoma and 31 intraepithelial neoplasia grade 3 (CIN3), previously characterized in terms of human papillomavirus (HPV) prevalence and genotype distribution, were analyzed for TP53 and PIK3CA mutations in the exons 4–9 and exon 9, respectively. RESULTS: Single nucleotide substitutions in TP53 and PIK3CA genes were detected in 36% and 11% of adenocarcinoma, in 16% and in 5% of squamous cell carcinoma, and in 13% and none of CIN 3, respectively. Nucleotide changes in TP53 were significantly more frequent in adenocarcinoma cases than in squamous cell carcinoma and CIN3 (P = 0.035) and were independent from HPV infection status. CONCLUSIONS: Mutations in the TP53 gene and to lesser extent in the PIK3CA gene seem more frequent in cervical adenocarcinoma than in squamous cell carcinoma and CIN3. Whether TP53 and PIK3CA gene mutations have an impact on prognosis and response to molecularly targeted therapies as well as in cytotoxic drugs in different cervical cancer histotypes needs to be analyzed in investigative clinical trials.